Exocytosis in mouse vestibular Type II hair cells shows a high‐order Ca2+ dependence that is independent of synaptotagmin‐4. Issue 14 (20th July 2020) - Spaiardi, Paolo; Marcotti, Walter; Masetto, Sergio; Johnson, Stuart L.
Abstract: Mature hair cells transduce information over a wide range of stimulus intensities and frequencies for prolonged periods of time. The efficiency of such a demanding task is reflected in the characteristics of exocytosis at their specialized presynaptic ribbons. Ribbons are electron‐dense structures able to tether a large number of releasable vesicles allowing them to maintain high rates of vesicle release. Calcium entry through rapidly activating, non‐inactivating CaV 1.3 (L‐type) Ca 2+ channels in response to cell depolarization causes a local increase in Ca 2+ at the ribbon synapses, which is detected by the exocytotic Ca 2+ sensors. The Ca 2+ dependence of vesicle exocytosis at mammalian vestibular hair cell (VHC) ribbon synapses is believed to be linear, similar to that observed in mature cochlear inner hair cells (IHCs). The linear relation has been shown to correlate with the presence of the Ca 2+ sensor synaptotagmin‐4 (Syt‐4). Therefore, we studied the exocytotic Ca 2+ dependence, and the release kinetics of different vesicle pool populations, in Type II VHCs of control and Syt‐4 knockout mice using patch‐clamp capacitance measurements, under physiological recording conditions. We found that exocytosis in mature control and knockout Type II VHCs displayed a high‐order dependence on Ca 2+ entry, rather than the linear relation previously observed. Consistent with this finding, the Ca 2+ dependence and release kinetics of the ready releasable pool (RRP) of vesicles were not affected by an absence of Syt‐4. However, we did find that Syt‐4 could play a role in regulating the release of the secondary releasable pool (SRP) in these cells. Our findings show that the coupling between Ca 2+ influx and neurotransmitter release at mature Type II VHC ribbon synapses is faithfully described by a nonlinear relation that is likely to be more appropriate for the accurate encoding of low‐frequency vestibular information, consistent with that observed at low‐frequency mammalian auditory receptors. Abstract : Here we show that the coupling between neurotransmitter release at the ribbon synapses of mature vestibular Type II hair cells display a high‐order dependence on calcium influx. The calcium dependence was not affected by an absence of the calcium‐sensing synaptic molecule synaptotagmin‐4, which has been shown to be involved in establishing the linear calcium dependence of high‐frequency auditory hair cells. Our findings suggest that a nonlinear exocytotic calcium dependence in vestibular hair cells is likely to be more appropriate for the accurate encoding of low‐frequency vestibular information.